Does a Pedestrian Environment Promote Walkability? Auditing a Pedestrian Environment Using the Pedestrian Environmental Data Scan Instrument - Wimbardana, Ramanditya; Tarigan, Ari K. M.; Sagala, Saut (Center for Research and Community Services ITB, 2018)
Abstract. This study was aimed at evaluating the pedestrian environment walkability from a residential area to a commercial area in Amherst, New York. An audit tool to record data of physical built environment elements was developed and tested. Data collection is integrated taking advantage of geo-spatial technology, so that pedestrian environment characteristics can be presented spatially. In this study, the Pedestrian Environmental Data Scan (PEDS) instrument was adopted to evaluate walkability in pedestrian environments. Thirteen variables were adopted to be used in this study: (1) segment type; (2) land use in the given segment; (3) slope; (4) segment intersection; (5) types of pedestrian facilities; (6) path condition; (7) number of trees shading walking areas; (8) crosswalks; (9) roadway/path lighting; (10) segment attractiveness for walking; (11) segment attractiveness for cycling; (12) segment safety for walking; and (13) segment safety for cycling. To collect and examine the data, the study integrated the audit tool with ArcGIS Online developed by ESRI. Overall, the selected road segments have the characteristics of a walkable environment between a residential area and a commercial area. The most convenient pedestrian environment was identified within the residential area because the sidewalks are attractive, are built on flat slopes, planted with dense shade trees, and have low-volume traffic. In the commercial area, the pedestrian environment is less attractive due to a lack of trees and less safety due to the mixed use of pedestrian pathways for store entrance. The results reflect the need for improvement of the audit tool in future studies.Keywords. walkability, GIS, environment audit, residential, commercial.Abstrak. Penelitian ini bertujuan untuk mengevaluasi pejalan kaki lingkungan pejalan kaki dari daerah pemukiman ke daerah komersial di Amherst, New York. Alat audit telah dikembangkan dan diuji untuk mencatat data unsur lingkungan fisik. Pengumpulan data terintegrasi dengan keuntungan teknologi geo-spasial untuk mengelola analisis, sehingga karakteristik lingkungan pejalan kaki akan disajikan secara spasial. Dalam studi ini, instrumen PEDS (The Pedestrian Environmental Data Scan) diadopsi untuk mengevaluasi walkability di lingkungan pejalan kaki. Tiga belas variabel diadopsi dari PEDS yang akan digunakan dalam penelitian ini, sebagai berikut 1) jenis segmen; 2) penggunaan lahan di segmen tertentu; 3) kemiringan lereng; 4) segmen persimpangan; 5) jenis fasilitas pejalan kaki; 6) kondisi jalan; 7) jumlah pohon yang menaungi area jalan; 8) penyeberangan; 9) penerangan jalan / jalan; 10) daya tarik segmen untuk berjalan; 11) daya tarik segmen untuk bersepeda; 12) keamanan segmen untuk berjalan; dan 13) keamanan segmen untuk bersepeda. Untuk mengumpulkan dan memeriksa data, studi ini mengintegrasikan alat audit dengan ArcGIS Online yang dikembangkan oleh ESRI. Secara keseluruhan, ruas jalan yang dipilih memiliki karakteristik untuk lingkungan walkable antara kawasan perumahan dan kawasan komersial. Lingkungan pejalan kaki yang paling nyaman diidentifikasi di daerah pemukiman karena trotoarnya menarik, dibangun di lereng datar, ditanami pohon teduh yang lebat, dan memiliki lalu lintas dengan volume rendah. Di kawasan komersial, lingkungan pejalan kaki kurang atraktif karena minimnya pepohonan dan kurang aman karena penggunaan jalan pejalan kaki yang beragam karena pintu masuk toko. Hasilnya mencerminkan kebutuhan perbaikan alat bantu audit di masa depan.Kata Kunci: ramah bagi pejalan kaki, GIS, audit lingkungan, hunian, komersial